Cyfrinach Craig Yr Wylan - Jones, Bet (Y Lolfa, 2014)
This is a first novel for children by a popular author. Huw and Jodie find themselves in trouble when they venture into an old tunnel underneath Huw's old home called Craig yr Wylan (The Seagull's Rock) by the sea.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books